2015
DOI: 10.1038/jcbfm.2015.179
|View full text |Cite
|
Sign up to set email alerts
|

The Indirect NMDAR Antagonist Acamprosate Induces Postischemic Neurologic Recovery Associated with Sustained Neuroprotection and Neuroregeneration

Abstract: Cerebral ischemia stimulates N-methyl-D-aspartate receptors (NMDARs) resulting in increased calcium concentration and excitotoxicity. Yet, deactivation of NMDAR failed in clinical studies due to poor preclinical study designs or toxicity of NMDAR antagonists. Acamprosate is an indirect NMDAR antagonist used for patients with chronic alcohol dependence. We herein analyzed the therapeutic potential of acamprosate on brain injury, neurologic recovery and their underlying mechanisms. Mice were exposed to cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…To test the BBB permeability, we infused the two drugs and Evans blue into tMCAO rats immediately and at 22 hours after reperfusion, respectively, and measured the Evans blue concentration in the contralateral and ipsilateral hemisphere at 24 hours after reperfusion. Consistent with the previous reports [ 28 ] , ischemia dramatically increased BBB permeability in the ipsilateral hemisphere, and more importantly, TR and edaravone rescued ischemia-induced BBB dysfunction ( Fig. 2H ).…”
Section: Resultssupporting
confidence: 93%
“…To test the BBB permeability, we infused the two drugs and Evans blue into tMCAO rats immediately and at 22 hours after reperfusion, respectively, and measured the Evans blue concentration in the contralateral and ipsilateral hemisphere at 24 hours after reperfusion. Consistent with the previous reports [ 28 ] , ischemia dramatically increased BBB permeability in the ipsilateral hemisphere, and more importantly, TR and edaravone rescued ischemia-induced BBB dysfunction ( Fig. 2H ).…”
Section: Resultssupporting
confidence: 93%
“…An imbalance in calcium homoeostasis has been shown to be associated with neurological diseases such as epilepsy, Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, stroke, and traumatic brain injury [33]. When given no later than 12 h after a stroke, even acamprosate showed neuroprotective efficacy and increased neurological recovery in an animal model [34]. The onset of Alzheimer's disease is potentially associated with previous calcium-signaling dysregulation and even low calcium content in drinking water [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors indicated the beneficial effects of NMDAR antagonists, primarily MK-801 and memantine, in various models of neuron damage including hypoxia-ischemia and harmful effects of oxygen and glucose deprivation (27,28). Doeppner et al showed that acamprosate, as indirect NMDAR antagonist, exhibited neuroprotective effects if administered 12 hours before stroke, through inhibition of calpain-mediated pro-injurious signaling cascades (29).…”
Section: Discussionmentioning
confidence: 99%